Cerebrovascular accidents in patients supported with veno-arterial extra-corporeal membrane oxygenation- is duration of support important?. (14th October 2021) - Hussain, S; Zero, N; Al-Saadi, T; Asghar, M; Glowacki, N; Andrade, A; Sciamanna, C; Joshi, A; Dia, M; Macaluso, G; Tatooles, A; Pappas, P; et al.
Abstract: Purpose of study: Veno-Arterial Extra-corporeal Membrane Oxygenation (VA-ECMO) is indicated for refractory cardiac and/or respiratory failure. Adverse events remain considerable despite best practices. We specifically aimed to understand risk factors associated with cerebrovascular accidents (CVA) in patients who underwent VA-ECMO support. Methods: We retrospectively assessed all VA-ECMO patients from 2007 to 2019 at our institution. We identified those who experienced a CVA while supported by VA-ECMO. Patients with the primary event (CVA) were matched to controls (no CVA) based on age and sex. Comparisons were made between groups using McNemar's, Mantel-Haenszel, and Wilcoxon Signed-Rank tests where appropriate. Results: Of the 278 VA-ECMO patients in the registry, 32 patients who experienced a CVA were identified; 24 (8.6%) ischemic and 8 (2.9%) hemorrhagic. Median age was 59.5 years (inter-quartile range: 49–65 years) and 75% of patients were males. Hypertension, diabetes, CAD and CHF were common co-morbidities (Table 1). Cardiogenic shock was the most common indication for VA-ECMO support in both cohorts, 75% in cases and 71.9% in controls. Cannulation strategies were identified as central or peripheral. There was a significant association of duration of VA-ECMO support with incidence of CVA, with a p-value of 0.03. Regression analysis showed a trend of increased risk of CVA by 4% for each additional day on VA-ECMO, however, this was not statistically significant (Odds ratio: 1.04; confidence interval 1.00–1.08). Most common outcome was death followed by decannulation to recovery and bridge to LVAD. Conclusion: Ischemic and hemorrhagic CVAs are not uncommon during VA-ECMO support. Our case control study shows an association of duration of VA-ECMO support with incidence of CVA. This underscores the importance of timely assessment and weaning or bridging of VA-ECMO patients to their next management step. FUNDunding Acknowledgement: Type of funding sources: None.